2003
DOI: 10.1110/ps.0350503
|View full text |Cite
|
Sign up to set email alerts
|

Matthews coefficient probabilities: Improved estimates for unit cell contents of proteins, DNA, and protein–nucleic acid complex crystals

Abstract: Estimating the number of molecules in the crystallographic asymmetric unit is one of the first steps in a macromolecular structure determination. Based on a survey of 15,641 crystallographic Protein Data Bank (PDB) entries the distribution of V M , the crystal volume per unit of protein molecular weight, known as Matthews coefficient, has been reanalyzed. The range of values and frequencies has changed in the 30 years since Matthews first analysis of protein crystal solvent content. In the statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
572
0
20

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 692 publications
(615 citation statements)
references
References 15 publications
23
572
0
20
Order By: Relevance
“…a part of the physiological substrate histone H3 and human cathepsin L by crystallizing the complex with a catalytic mutant of the enzyme and elucidating its structure [16]. Refinement confirmed the positioning of only three amino acids from the histone H3 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] peptide. Our crystal packing analysis suggested that there is not enough space to accommodate all 14 peptide residues in the available space in the active site cleft.…”
Section: Abstract: Cathepsin; Cysteine Cathepsin; Substrate Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…a part of the physiological substrate histone H3 and human cathepsin L by crystallizing the complex with a catalytic mutant of the enzyme and elucidating its structure [16]. Refinement confirmed the positioning of only three amino acids from the histone H3 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] peptide. Our crystal packing analysis suggested that there is not enough space to accommodate all 14 peptide residues in the available space in the active site cleft.…”
Section: Abstract: Cathepsin; Cysteine Cathepsin; Substrate Interactionmentioning
confidence: 99%
“…The data set was processed with the XDSAPP [20] and scaled in the P212121 space group. The Matthews coefficient analysis [21] unambiguously defined one molecule in the asymmetric unit. The structure of cathepsin L-C25S was determined using PHASER [22] with the cathepsin L structure (PDB ID 2YJ2) [23] as the search model.…”
Section: Crystallization and Structure Determination Of Human Cathepsmentioning
confidence: 99%
“…During the dehydration process the unit-cell volume of the crystals decreased by 13.6%, which corresponded to a significant reduction of solvent content from 64.5 to 58.9% (Kantardjieff & Rupp, 2003;Fig. 3c).…”
Section: Crystal Diffraction and Dehydrationmentioning
confidence: 96%
“…R meas = P h ½n h =ðn h À 1Þ 1=2 P n h i jhI h i À I h;i j= P h P n h i I h;i , where n h is the multiplicity, I h,i is the ith intensity of reflection h and hI h i is the weighted average intensity for all observations i of reflection h. R merge-F = ð P jA I h;P À A I h;Q jÞ=ð 1 2 P A I h;P À A I h;Q Þ, where I h,P and I h,Q represent the partially averaged intensities (Diederichs & Karplus, 1997). ‡ The most probable solution according to statistical sampling (Kantardjieff & Rupp, 2003). However, it also has the lowest sequence identity of the domains compared with the SERCA1a search model (28% compared with 38% overall), with truncations and deletions of secondary-structure elements and loop regions, which may in part explain this observation.…”
Section: Structure Determination and Analysismentioning
confidence: 99%